2018
DOI: 10.18291/njwls.v8i3.109543
|View full text |Cite
|
Sign up to set email alerts
|

After the Great Recession: Unions’ Views on Transnational Interests and Cooperation

Abstract: The aim is to describe and explain the similarities and differences between European trade unions concerning their views on transnational union interests and cooperation in the wake of the Great Recession. We do this by analyzing 221 responses from a European-wide web/postal survey distributed in 2015-2016 to union officials representing staff in employment sectors such as transport, metal and mining, construction, health care, and banking and finance. We find only limited sectoral differences, despite the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The results indicate that the crisis had ambiguous effects on sectoral-level cooperation: over 60 percent of respondents agreed that it had made unions more protectionist, but over 70 percent stated that it had increased their own cooperation with other unions in Europe (Bengtsson and Vulkan, 2018). Over 40 percent reported that their unions desire more transnational cooperation in the future, and 74 percent stated that they would prefer more transnational cooperation in their sector rather than within their own countries.…”
Section: Resultsmentioning
confidence: 97%
“…The results indicate that the crisis had ambiguous effects on sectoral-level cooperation: over 60 percent of respondents agreed that it had made unions more protectionist, but over 70 percent stated that it had increased their own cooperation with other unions in Europe (Bengtsson and Vulkan, 2018). Over 40 percent reported that their unions desire more transnational cooperation in the future, and 74 percent stated that they would prefer more transnational cooperation in their sector rather than within their own countries.…”
Section: Resultsmentioning
confidence: 97%
“…With a few select partners, they even had a steady working group to develop joint strategies on industrial policy (#11 DE). As previous research shows, the issues and intensity of cooperation vary not only between sectors and regimes but also within, depending on resources and interests (Bengtsson and Vulkan, 2018; Vulkan and Larsson, 2018). The joint interest to cooperate may thus vary with different bilateral partners – as illustrated by one Swedish representative:With the Germans, [cooperation] is mainly about politics, economy, industrial policy […] With the French [and] the Dutch, it is a lot more related to companies, company issues, restructuring, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…Even more important is whether the affiliates want to be coordinated and the importance they attach to the European level – and the role of the ETUFs more specifically – in pursuing their interests within the multi-level European polity. Comparative studies illustrate that depending on their situation in the national context the views of national trade unions differ considerably (Bengtsson and Vulkan, 2018; Larsson, 2015). In a nutshell, there are two extreme positions.…”
Section: Logic Of Membership: the Art Of Managing Diversitymentioning
confidence: 99%